Pelatihan Literasi Dasar Bermuatan Pendidikan Inklusif bagi Guru TK Aisyiyah 2 Aimas - Adi Iwan Hermawan; Desti Rahayu; Khaila Fezya Putri; Salomina Burdam (Pusat Riset dan Inovasi Nasional, 2026)
Early childhood education is a fundamental phase in the formation of children's character, literacy skills, and social skills. However, children's basic literacy skills in various regions of Indonesia, including Aisyiyah 2 Aimas Kindergarten, Southwest Papua, are still relatively low, exacerbated by limited learning media, conventional teaching approaches, and teachers' lack of understanding of inclusive education and positive discipline. This study aims to analyze the implementation of basic literacy training with inclusive education and its impact on improving teacher competence. The method used is a one group pretest in the context of community service, involving six teachers as subjects. The program is carried out through three stages: pre-training (observation, interview, and pretest), training (literacy materials based on the DUBT model—Listen, Speak, Read, Write; inclusive education; and positive discipline), and post-training (posttest, classroom observation, reflection, and mentoring). The results showed a significant increase in teacher competence, as shown by the increase in the average pretest score from 57.5 to 84.8 in the posttest. In addition, 83% of teachers are able to implement literacy practices such as reading picture stories, letter cards, reading corners, and dialogue interactions with children. Teachers also began to show acceptance of children's diversity and applied positive discipline without punishment. These findings show that inclusion-based literacy training is effective in improving teachers' pedagogical knowledge and practices. This research emphasizes the importance of developing adaptive, humanist, and equitable literacy as the foundation of early childhood learning.